Contextualisation of the gospel among Muslims - M. Coleman; P. Verster (Acta Theologica)
Contextualisation is considered crucial in relating the gospel to culture. However, when reaching Muslims by means of the Christian gospel it is also important to evaluate the concept of contextualisation, as different approaches enable one to understand the mission to Muslims in different ways. There are still divergent views ranging from total rejection of any aspect of the Muslim culture and beliefs to full acceptance of the Muslim religious culture. Various exponents have attempted in different ways to deal with the issue. Phil Parshall is regarded as a leader in this field. This article suggests a holistic Scriptural view rather than accepting contextualisation as a means to relate the gospel to Muslims. This view is intrinsically bound to Scripture and the acceptance of Scripture as the revelation of God. It is argued that Muslims should be approached with great respect while emphasising the true revelation of God in Christ.